PERAN KURIKULUM PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK PANDANGAN SISWA TENTANG "DIRI" DAN "ORANG LAIN” - Rohmatun Fitriana; Rohmatin Ramadhani; M.Fathy ubaidillah; Rifqi Khairul Anam (As-Sulthan Journal of Education, 2025)
This study examines the role of the Islamic Education (PAI) curriculum in shaping students’ Islamic identity, self-perception, and perspectives toward “otherness” within Indonesia’s multicultural society. Ideally, the PAI curriculum is designed to internalize universal Islamic values such as justice, compassion, and toleranceyet in practice it still shows a significant gap between its conceptual goals and classroom implementation. PAI learning in many schools tends to be doctrinal, mono-narrative, and lacking in dialogic space, which may contribute to the development of exclusive attitudes among students. Using a library research method with content analysis of journals, books, and official documents, this study finds that the PAI curriculum holds great potential for strengthening students’ religious and moral identity but remains limited in cultivating inclusive attitudes toward diversity. The findings also highlight the need for curriculum reformulation that is more contextual, dialogical, and multicultural through learning strategies that emphasize universal human values, empathy, and social awareness. A socially and globally responsive PAI curriculum is considered essential for shaping a generation of moderate, humanistic Muslims who are capable of living harmoniously in a plural society.